(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research explores the effectiveness of high school teachers, focusing on variations related to gender, marital status, and teaching experience. Using a normative survey method, 450 teachers (305 males, 145 females) were sampled from government and private high schools in the Kulgam district of Jammu and Kashmir. The Teacher’s Effectiveness Scale (TES), developed and validated by the researcher in 2018, measured teacher effectiveness. Analysis of the data, conducted using SPSS, .The findings indicated an average effectiveness rating for high school teachers. Notably, a significant difference in effectiveness was observed between male and female teachers, while no such distinctions were found based on marital status or teaching experience. These findings have implications for educational policies and interventions to enhance teacher effectiveness.